(untitled) (Journal of the Association for the Study of Australian Literature, 2013)
A wide-ranging consideration of the struggle between nature and culture in Australia, evident in its cities. The article discusses writing by D.H.Lawrence, Murray Bail, Les Murray, Peter Carey, Ada Cambridge and many others and focuses on Sydney.